BI Rate The FED Rate dan Inflasi Terhadap Indeks Harga Saham Gabungan - Muhammad Attallah Al Faruqi; M.B. Nani Ariani; Fachru Nofrian (Jurnal Indonesia Sosial Sains, 2022)
The Composite Stock Price Index certainly continues to fluctuate or change, where these changes occur due to various macroeconomic factors that influence it, namely the BI Rate, The FED Rate, and inflation. This study aims to determine the effect of fluctuations in the BI Rate, The FED Rate, and inflation on the Composite Stock Price Index. This study uses data from 1989 to 2019. The method in this study is a multiple linear regression analysis models using the OLS method. The results of multiple linear regression analysis prove that there is a significant effect between the BI Rate on the Composite Stock Price Index, there is no significant effect between The FED Rate on the Composite Stock Price Index, and there is a significant effect between inflation on the Composite Stock Price Index. The conclusion of this study is moderate inflation and the government's target level shows that economic conditions are stable, not sluggish, and still support the level of trading that allows investors to invest in stocks with rising inflation by investing capital in stocks for speculatively motivated trading.